Heiserkeit - Welsch, Katja; Stern, Cornelia; Schreiber, Thomas; Lorenz, Daniel (Deutsche Heilpraktiker-Zeitschrift, 2023)
Die Autoren stellen jeweils eine Behandlungsstrategie gegen Heiserkeit vor.
Keywords: Heiserkeit